1992
DOI: 10.3109/08916939209150322
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Immune Hemolytic Anemia With A High Thermal Amplitude, Low Affinity IgG Anti-Pr a Cold Autoantibody

Abstract: A 54 y.o. woman presented with acute Coombs-negative hemolytic anemia at an outside hospital where she received 25 RBC transfusions and did not respond to prednisone or splenectomy. On transfer to our hospital, routine DAT and IAT were weakly positive, occasionally negative. When a modified "cold" antiglobulin test was employed, the result was strongly positive for IgG, weakly positive for C3d. Cold agglutinin titer was 32, and the Donath-Landsteiner test was negative. The autoantibody exhibited Pra specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The hemolysis was not associated with activation of complement by either the classic or the alternative pathways despite the patient's serum containing complement responsive to activation by both pathways. The immunoglobulin isotypes of the anti-Pr CAs in patients with severe or fatal hemolysis have varied: monoclonal 2,19,20 and polyclonal IgG, 21 an IgA (D. Roelcke, personal communication, 1999), and five due to IgM. 3,5,8,[22][23][24] Evidence for complement activation was reported in some patients, 22,23 variable in some patients, 19,21 and not reported in others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemolysis was not associated with activation of complement by either the classic or the alternative pathways despite the patient's serum containing complement responsive to activation by both pathways. The immunoglobulin isotypes of the anti-Pr CAs in patients with severe or fatal hemolysis have varied: monoclonal 2,19,20 and polyclonal IgG, 21 an IgA (D. Roelcke, personal communication, 1999), and five due to IgM. 3,5,8,[22][23][24] Evidence for complement activation was reported in some patients, 22,23 variable in some patients, 19,21 and not reported in others.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoglobulin isotypes of the anti-Pr CAs in patients with severe or fatal hemolysis have varied: monoclonal 2,19,20 and polyclonal IgG, 21 an IgA (D. Roelcke, personal communication, 1999), and five due to IgM. 3,5,8,[22][23][24] Evidence for complement activation was reported in some patients, 22,23 variable in some patients, 19,21 and not reported in others. 2,20,24 The use of the fluorescent probe Fluo-3 to estimate intracellular Ca 2+ and the large gradient of Ca 2+ across the membrane of RBCs permits rapid 25 These authors, furthermore, showed that binding of this PE to cinnamycin interfered with cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The auto-antibody was a polyclonal IgG, of high thermal amplitude, low affinity, and with Pra specificity, titer 1:4,000. A detailed description of the serologic investigations was reported by Ramos et al [14]. During her first 74 days of hospitalization she required an average of one red cell transfusion (PRC) daily.…”
Section: Methodsmentioning
confidence: 99%
“…IgG CAs are rare. Ten cases were reviewed in 1990, 14 and an additional case was reported in 1992 15 . At least 5 of the 11 patients had severe hemolysis (Hb <7 g/dL), and 3 had a negative DAT.…”
Section: Discussionmentioning
confidence: 99%